2019
DOI: 10.1177/0022034519864592
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Lineage and Signaling in Murine Salivary Glands

Abstract: Maintaining salivary gland function is critical for oral health. Loss of saliva is a common side effect of therapeutic irradiation for head and neck cancer or autoimmune diseases such as Sjögren’s syndrome. There is no curative treatment, and current strategies proposed for functional regeneration include gene therapy to reengineer surviving salivary gland tissue, cell-based transplant therapy, use of bioengineered glands, and development of drugs/biologics to stimulate in vivo regeneration or increase secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…In addition, several supportive cell and tissue types are disrupted during dissociation and may be required to enhance longitudinal SGm function. These tissues include vasculature, nerves, and mesenchyme, which are intrinsic to salivary gland development, homeostasis, and regeneration 13 – 15 , 112 . For example, primary embryonic mesenchyme supported salivary organoid formation with robust AQP5 expression in co-culture with E16 salivary epithelium 113 , 114 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several supportive cell and tissue types are disrupted during dissociation and may be required to enhance longitudinal SGm function. These tissues include vasculature, nerves, and mesenchyme, which are intrinsic to salivary gland development, homeostasis, and regeneration 13 – 15 , 112 . For example, primary embryonic mesenchyme supported salivary organoid formation with robust AQP5 expression in co-culture with E16 salivary epithelium 113 , 114 .…”
Section: Discussionmentioning
confidence: 99%
“…Krt5 + cells have also been reported to generate acinar cells upon severe injury ( Weng, et al., 2018 ), and lineage tracing studies have shown that Krt5+ BD cells act as progenitors for GCTs and SD cells ( Aure, et al., 2019 ). Little is understood about the factors driving BD cell differentiation and maturation, as well as those involved in their plasticity to regenerate acinar cells.…”
Section: Resultsmentioning
confidence: 99%
“…This, we suspect, is largely due to the relative ease with which SMGs can be dissected, unlike PGs, which are considerably smaller in mice and tucked away in a rather inaccessible site. However, given the importance of the PG in normal development and the disease context, it is imperative that any studies on the SG also take into account unique and common molecular attributes of all glandular subtypes, especially the PG (Aure et al 2019). Here we have extended our prior genomic studies on the SG and focused on the PG, with a goal to better identify the genes that are expressed during various stages of gland maturation and, importantly, enriched in the PG.…”
Section: Discussionmentioning
confidence: 99%